THE EFFECT OF GUANO FERTILIZER APPLICATION ON THE GROWTH OFTOMATO PLANTS (Solanum lycopersicum L.) - Komalasari; Maghfiroti, Ukky; Fatika Sari, Cindy; Santi Andarista, Chikal (Syarif Hidayatullah State Islamic University Jakarta, 2025)
The high market demand for tomatoes is driven by increasing public consumption from year to year. This high market demand encourages farmers to increase tomato production with superior quality. Guano fertilizer has strategic value for increasing productivity and quality of tomatoes. The use of environmentally friendly and easily accessible guano fertilizer will reduce farmers' dependence on relatively expensive chemical fertilizers, thereby increasing production cost efficiency. This study not only aims to identify the optimal dose of guano fertilizer for tomato growth, but also contributes to the development of a productive, efficient, and environmentally friendly agribusiness production system. This study used a Completely Randomized Block Design with a single factor: guano fertilizer dosage (0, 26, 51, and 71 g per pot), with nine replications, totaling 36 experimental units. The experiment was conducted in a greenhouse using soil media in 19 cm pots diameter, from March 13 to May 8, 2023. Guano fertilizer was applied once 10 days after planting (DAP). Observations on plant height, number of leaves, and leaf area were taken biweekly from 14 to 56 DAP. Data were analyzed using Analysis of Variance in SPSS, followed by Duncan's Multiple Range Test at a 5% significance level. The results showed that the dose of guano fertilizer that significantly affected the increase in plant height, leaf area and number of leaves of tomato plants was dose 2 of 51 grams.